Direct reprogramming of adult somatic cells toward adventitious root formation in forest tree species: the effect of the juvenile–adult transition - Díaz-Sala, Carmen (Frontiers in Plant Science, 2014)
Cellular plasticity refers, among others, to the capability of differentiated cells to switch the differentiation process and acquire new fates. One way by which plant cell plasticity is manifested is through de novo regeneration of organs from somatic differentiated cells in an ectopic location. However, switching the developmental program of adult cells prior to organ regeneration is difficult in many plant species, especially in forest tree species. In these species, a decline in the capacity to regenerate shoots, roots or embryos from somatic differentiated cells is associated with tree age and maturation. The decline in the ability to form adventitious roots from stem cuttings is one of the most dramatic effects of maturation, and has been the subject of investigations on the basic nature of the process. Cell fate switches, both in plants and animals, are characterized by remarkable changes in the pattern of gene expression, as cells switch from the characteristic expression pattern of a somatic cell to a new one directing a new developmental pathway. Therefore, determining the way by which cells reset their gene expression pattern is crucial to understand cellular plasticity. The presence of specific cellular signalling pathways or tissue-specific factors underlying the establishment, maintenance and redirection of gene expression patterns in the tissues involved in adventitious root formation could be crucial for cell fate switch and for the control of age-dependent cellular plasticity.